The Battle of Britain on screen: 'the few' in British film and television drama - Mackenzie, S. P. (Societies at war, 2007)
The battle foretold : The lion has wings (1939) -- Spitfire of dreams : The first of the few (1942) -- One for all : Angels one five (1952) -- All for one : Reach for the sky (1956) -- The big picture : The Battle of Britain (1969) -- Catalogue of error : Piece of cake (1988) -- The fighter boys : A perfect hero (1991)
https://katalog.adlr.link/Record/0-525143092